Qualities of an Effective Teacher: The Perspectives of Tertiary- Level Students in Bangladesh (Global Journal of Human-Social Science, 2023)
Effective teaching involves valuable interactions between teachers and students which can facilitate students learning process It makes a positive impact on the learners learning process Good teachers are a part and parcel of effective teaching They can make a congenial learning environment inside the classroom and motivate their students Effective instructors play a vital role in the academic field of tertiary-level students They can guide their students to build up their academic as well as future professional skills Good teachers can also increase the curiosity of the students to learn new things by implementing different teaching techniques inside the classroom In a developing country like Bangladesh some teachers are not qualified enough and they lack sufficient training Effective teachers are inadequate in the context of Bangladesh The main objective of this study is to identify the qualities that teachers should have to make their students efficient in every sphere of life This study is also important for understanding the contributions of good teachers to students academic performances The researcher followed qualitative methods for this study The researcher took semi-structured interviews of ten participants all drawn from a private university in Bangladesh Based on primary data the researcher found that teachers have both positive as well as negative qualities for instance classroom management loving and monitoring their students creating effective communication biased strict and commercial mindset etc This study explored the qualities that students expect from their teachers the challenges students face while becoming effective teachers and some suggestions through which students can become good teachers in the future
Keywords: effective teaching; teachers; training; qualitative methods; positive; negative qualities; effective communication